2015
DOI: 10.1103/physrevlett.114.117002
|View full text |Cite
|
Sign up to set email alerts
|

Detection of an Unconventional Superconducting Phase in the Vicinity of the Strong First-Order Magnetic Transition in CrAs UsingAs75-Nuclear Quadrupole Resonance

Abstract: Pressure-induced superconductivity was recently discovered in the binary helimagnet CrAs. We report the results of measurements of nuclear quadrupole resonance for CrAs under pressure. In the vicinity of the critical pressure Pc between the helimagnetic (HM) and paramagnetic (PM) phases, a phase separation is observed. The large internal field remaining in the phase-separated HM state indicates that the HM phase disappears through a strong first-order transition. This indicates the absence of a quantum critica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
75
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 22 publications
(45 reference statements)
6
75
0
2
Order By: Relevance
“…The P dependent phase diagram is reminiscent of doped iron based superconductors. Moreover, nuclear quadrupole resonance results indicate that it is a unconventional superconductor [14].…”
Section: Introductionmentioning
confidence: 99%
“…The P dependent phase diagram is reminiscent of doped iron based superconductors. Moreover, nuclear quadrupole resonance results indicate that it is a unconventional superconductor [14].…”
Section: Introductionmentioning
confidence: 99%
“…The findings were later confirmed by Kotegawa et al [17] and their subsequent 75 As-nuclear quadrupole resonance (NQR) study evidenced no coherence effect in the nuclear spin relaxation rate 1/T1, thus suggesting an unconventional nature for the observed SC in CrAs. [18] These observations make CrAs an ideal material for in-depth studies on how the coupled structural and helimagnetic orders are tuned to the critical point and how the magnetism is coupled to the unconventional SC developed nearby. In combinations of elastic and inelastic neutron scattering, resistivity, and specific-heat measurements on undoped CrAs and P-doped CrAs1-xPx single crystals and powders, we have studied systematically the evolutions of static helical order and dynamic spin correlations as well as the electronic properties of CrAs when its coupled structural/helical order is suppressed by either external pressure or the chemical substitutions.…”
mentioning
confidence: 99%
“…In addition, a recent high-pressure NQR study on CrAs single crystals also found no clear signature of a change in the magnetic structure under pressure. [18] If we assume that the helical structure does not change other than  with pressure and normalize the magnetic signal by the (020) nuclear Bragg intensity, the ordered magnetic moment at 6.9 kbar, which is proportional to the square root of the magnetic intensity, is estimated to be ~ 65% of that at ambient pressure. This estimated moment is between those two polycrystalline results (~25% [26] and ~85% [27]).…”
mentioning
confidence: 99%
“…Their superconducting mechanism shown in many experimental results [13][14][15][16] is very likely related to electron-electron interactions. Among the families of the chromium-based superconductors, the Q1D A 2 Cr 3 As 3 (A=K,Rb,Cs) superconductors family [10][11][12] , which has T c up to 6.1 K 10 at ambient pressure, is particularly intriguing.…”
mentioning
confidence: 99%